A Case of Anterior Mediastinal Mass treated as Bronchial Asthma. - Dr. Renuka Jadhav; Dr. Pooja Motwani; Dr. Sharad Agarkhedkar (Pediatric Review: International Journal of Pediatric Research, 2021)
Anterior Mediastinal Masses (AMM) can range in presentation from an asymptomatic incidental finding to significant cardiorespiratory compromise. Symptoms do not always correlate to the degree of compression. Patients with AMM are at high risk for hemodynamic instability and cardiovascular arrest with induction of anesthesia. This report describes a child with a large AMM who presented with classic symptoms of recurrent wheezing and was inadequately evaluated. It is imperative, especially in these unexpected presentations, to have a high index of suspicion.